Implementasi Metode Jet Tempur Dalam Meningkatkan Bimbingan Baca Tulis Al Qur’an Di MTs Negeri 1 Kota Kediri - Mu'min Ali Murtado; Miftahudin (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
The implementation of Jet Tempur Method can improve Al Qur'an reading guidance at Lirboyo Islamic Boarding School. These preliminary data form the basis of this research in First Middle School Of Islamic State 1 Kediri City. This research uses a descriptive qualitative approach by exploring data in depth according to the focus of the study. Data collection by observation, interview and documentation. After the data is collected and analyzed qualitatively, the data is processed by data reduction, data presentation and drawing conclusions. The results showed that (1) ustadaz at First Middle School Of Islamic State 1 Kediri had implemented Al Qur'an reading and writing guidance, with the jet fighter method well starting the planning, implementation and follow-up stages of the implementation of the fighter jet method which had given a good impact on students, (2) the results of the learning of reading and reading guidance of the Qur'an can be known through daily demonstrations by asking students to face their teacher and then evaluating and formative exams, final semester exams.